Nanophotonic antennas unveil the nanoscale mechanisms of disease.
Full understanding of the living cell is now within reach thanks to recent advances in nanophotonics. EU researchers have managed to bring nano-antennas to the biological domain-something that had never been achieved before. Collaborations with major industry players have already begun.